Penyetaraan Nilai Viskositas terhadap Indeks Bias pada Zat Cair Bening - Eka Jati, Bambang Murdaka; Karyono, Karyono; Supriyatin, Supriyatin (BERKALA FISIKA, 2010)
The research to find out of the relation between viscosity of the liquid (using Viscosimeter Ostwald) to their indeks of refraction (using ABEE refractometer) have been done. It has been chossed the solution of sugar and also solution of salt, at some percentage of concentration (shown on that density variation), and measured their viscosity. Then, those solutions are measured their indeks of refraction. After that, it would be found the relation between their viscosity to their indeks of refraction. The conclusion, it could be found quite linearly graph of viscosity to indeks of refraction of sugar and salt solution for 10 up to 100% in concentration. This relation depends on kind of solution. Â Key words: viscosity, indeks of refraction, transparent liquid